I, Houdini : the amazing story of an escape-artist hamster - Reid Banks, Lynne, 1929-; Riley, Terry (New York : Avon, 1989)
A boastful hamster with exceptional talent as an escape artist recounts his experiences during his quest for the great outside.
Keywords: Hamsters -- Juvenile fiction; Hamsters -- Fiction; Hamsters -- Fiction